Home to Roost: Some Problems for the Nested-Types Theory of Musical Works, Versions, and Authentic Performance - Andrew Kania (Estetika, 2022)
A critical note on Nemesio G. C. Puy, ‘Interpretive Authenticity: Performances, Versions, and Ontology’, 'Estetika' 59 (2022): 135–52.